Kompleksitas Manusia Seiring Perkembangan Makro Ekonomi: Analisis Mendalam - Evi Putri Rahmadani; Ayun Triska Yahesa; Ilmia Nur Khofifah; Siti Darni; Eli Masnawati (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
This study explores human complexity and its impact on macroeconomic development. The main focus is on the buyer's mental variables, such as financial assumptions and courage, and how these elements influence business utilization and behavior. Information from measured studies and investigations shows that positive monetary assumptions will often strengthen financial movements, while vulnerabilities or negative assumptions can hinder monetary developments. The proposed strategy suggestions include clear correspondence to rebuild public confidence and appropriate monetary enhancement arrangements. By understanding these elements, this exploration provides further insight into the collaboration between shopper brain science and macroeconomics, which is important for planning compelling strategic systems in the face of advanced economies.